Evaluasi Keberlanjutan Pertanian Jagung dalam mendukung Ketahanan Pangan (Studi Kecamatan Sawerigadi Kabupaten Muna Barat Indonesia) - La Ode Muhammad Iksan Yusuf; Muhammad Firmansyah; Masyitah Masyitah; Sulistiani Syafitri (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Corn farming plays a strategic role in supporting food security and agricultural development, especially in rural areas that depend on local food commodities. Although various approaches have assessed the sustainability of corn farming at the regional and national levels, empirical studies at the subdistrict level that simultaneously integrate five dimensions of sustainability are still limited. This study aims to evaluate the level of sustainability of the corn farming system in supporting food security in Sawerigadi Subdistrict, West Muna Regency. Data were obtained through field observations, in-depth interviews, measured questionnaires, and Focus Group Discussions with farmers and farmer group leaders, as well as supported by secondary data. Sustainability analysis was conducted using a multidimensional approach covering economic, ecological, socio-cultural, institutional, and technological dimensions. The results show that the corn farming system is in the moderately sustainable category with an index value of 54.05. The economic and ecological dimensions are classified as moderately sustainable, while the socio-cultural dimension shows relatively better performance. Conversely, the institutional and technological dimensions are still in the less sustainable category. Sensitive attributes that affect sustainability are mainly related to the limitations of farmer institutions, low adoption of cultivation technology, and suboptimal market access. The main scientific contribution of this study is the provision of a multidimensional approach-based corn farming sustainability evaluation framework that empirically identifies the key dimensions and attributes that determine sustainability at the local level. These findings provide a scientific basis for the development of strategies to strengthen a more sustainable corn farming system in support of local food security.